Christmas 101 : celebrate the holiday season, from Christmas to New Year's - Rodgers, Rick, 1953- (New York : Broadway Books, 1999)
Provides recipes and entertaining tips for Christmas and New Year's Eve meals and parties
Keywords: Christmas cooking